Peningkatan Kemampuan Menyimak Pembelajaran Peserta Didik Melalui Media Poadcast Pada Mata Pelajaran Bahasa Indonesia - vitri yanti; rahmi (Universitas Negeri Padang, 2023)
This study aims to determine the role of podcast learning media in Indonesian language learning which focuses on listening to students on the subject of poetry.The research model used is the ADDIIE model which has five stages of development, namely the development stage, implementation stage, and evaluation stage. In this study, it was taken from an observation questionnaire conducted on a number of junior high school students. The Poadcast learning media or audio-radio-based learning media at this time can be accessed on several social media platforms such as Spotify, Joox, and others that can be accessed anytime. Any where by students. Nowadays, the average junior high school student already has an android, so it would be great if a teacher could learn by using podcasts as a media to support learning. The results showed that the use of podcasts or based Audio visuals are very helpful in improving students' listening skills because in terms of learning media, podcasts are very attractive to students compared to listening to directions from teachers manually in front of the class.